2017
DOI: 10.1007/s40071-017-0173-2
|View full text |Cite
|
Sign up to set email alerts
|

Tetraselmis chuii biomass as a potential feed additive to improve survival and oxidative stress status of Pacific white-leg shrimp Litopenaeus vannamei postlarvae

Abstract: Shrimp is an important traded fishery commodity. When subjected to stress, shrimp usually suffers from oxidative stress, which leads to cell injury, senescence, and death. To maintain shrimp good health, performance and production, antioxidant and immune systems are important. Natural antioxidants found in microalgae may be used to increase the cell protection against oxidative damage, being a promising alternative to the carcinogenic synthetic antioxidants. In this study, Tetraselmis chuii was evaluated for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…This protein fraction includes antioxidant enzymes, such as superoxide dismutase (SOD), catalase and glutathione peroxidase, that repair or prevent cellular damage caused by reactive oxygen species, [44] , [45] , [46] , [47] . Microalgae produce antioxidant molecules when exposed to nutrient-limiting conditions [35] and can improve survival and resistance to salinity stress of prey organisms such as the Pacific white-leg shrimp post-larvae [48] . A previously reported method for precipitation and concentration of low molecular weight proteins using organic solvents [34] was customized in the present study (see, method details section).…”
Section: Additional Informationmentioning
confidence: 99%
“…This protein fraction includes antioxidant enzymes, such as superoxide dismutase (SOD), catalase and glutathione peroxidase, that repair or prevent cellular damage caused by reactive oxygen species, [44] , [45] , [46] , [47] . Microalgae produce antioxidant molecules when exposed to nutrient-limiting conditions [35] and can improve survival and resistance to salinity stress of prey organisms such as the Pacific white-leg shrimp post-larvae [48] . A previously reported method for precipitation and concentration of low molecular weight proteins using organic solvents [34] was customized in the present study (see, method details section).…”
Section: Additional Informationmentioning
confidence: 99%
“…Zhang et al (2013) observed that the addition of astaxanthin to Pacific white shrimp diets could enhance shrimp growth and reduce free reactive oxygen species (ROS) which subsequently reduced antioxidant gene expression of superoxide dismutase (SOD) and catalase. In another study, using the green microalgae T. chuii as an additive feed for L. vannamei larvae could increase larval growth and antioxidant activity while reducing stress (Rahman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The microalgae (Schizochytrium sp., Chlorella vulgaris, Amphora coffeaformis, Schizochytrium limacinum, Acutodesmus obliquus, Nannochloropsis spp., Tetraselmis chuii and Botryococcus braunii) were mostly included in the animal feed as dry microalgae with a percentage of inclusion mainly going from 1-10% or as a molecule equivalent of given antioxidant compounds. The results are variable depending on species from no effect of the microalgae tested [120,123] to a decrease in oxidative stress measurements such as the malondialdehyde or hydrogen peroxide content [124][125][126][127][128][129] or a decrease in DNA damage [123]. In most cases, it seems that the inclusion of microalgae directly in the fed has a positive effect on the animal physiology, which is promising regarding further used of microalgae in the food industry either in human or animal nutrition as functional ingredients.…”
Section: Antioxidant Activity Of Microalgaementioning
confidence: 99%